Hubungan Paritas Dengan Kejadian Kanker Serviks: Tinjauan Pustaka - Nathasya Karren Zeta Nathasya Karren Zeta; Rasmi Zakiah Oktarlina; Dwi Aulia Ramdini; M. Fitra Wardhana (CV. Jasa Sukses Abadi, 2023)
Cervical cancer is a malignancy of the uterine cervix. Cervical cancer is one of the cancers that most often causes death in women in the world, especially in developing countries where one of the main causes is infection with the Human Papilloma Virus (HPV). The incidence of cervical cancer both in Indonesia and in the world tends to increase from year to year. The latest data shows that in 2018 there were 570,000 cases of cervical cancer in the world and in 2013 as many as 98,692 cases of cervical cancer occurred in Indonesia. According to the American Cancer Society, factors that can increase the risk of developing cervical cancer are HPV infection, family history of cervical cancer, use of hormonal birth control types, sexual behavior, age, parity, inappropriate diets that tend to be unhealthy diets and smoking habits. The number of parity of a woman associated with the incidence of cervical cancer. This is because every delivery, the cervix will experience trauma during the remodeling process. Deviations during the remodeling process cause changes in the extracellular components which impact important molecules that act as anticancer, namely E-Cadherin where the content will decrease in the cervical membrane so that the risk of cervical cancer will increase.